3. EVALUATION OF THE RESULTS OF TREATMENT OF ACUTE HYPERTRIGLYCERIDEMIC PANCREATITIS WITH INSULIN AT VIET DUC GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate the effectiveness of insulin therapy in patients with hypertriglyceridemic acute pancreatitis at Viet Duc General Hospital from February 2022 to November 2023.Subjects and Methods: A prospective descriptive study was conducted on 24 patients diagnosed with hypertriglyceridemic acute pancreatitis, admitted to and treated in the Emergency Resuscitation Department of Viet Duc General Hospital from February 2022 to November 2023.Results: The average age of the study group was 39.04 ± 9.5 years. Clinical: All patients (100%) experienced abdominal pain; 91.6% had abdominal distension, and 41.6% had progressive intestinal obstruction.Paraclinical: Blood triglyceride levels were elevated, with an average value of 23.5 ± 7.9 mmol/L, accompanied by increased cholesterol levels averaging 14.4 ± 7.1 mmol/L. Blood glucose levels were also elevated, with an average concentration of 12.1 ± 5.3 mmol/L. Treatment: High-dose insulin infusion (0.1–0.2 IU/kg/h) was required in 62.5% of patients. The average duration of insulin therapy was 32 ± 17.7 hours, with most patients receiving insulin treatment within 24 hours.Treatment Outcomes: There were no fatalities, and 87.5% of patients achieved recovery.Conclusions: The most common symptoms of acute pancreatitis included abdominal pain and elevated triglyceride and glucose levels. High-dose insulin was effective in treatment, particularly in diabetic patients, and was combined with other methods such as optimized fluid resuscitation, antibiotic therapy, and nasogastric tube placement.
Keywords: acute pancreatitis; hypertriglyceridemia; insulin